Altered tetrahydrobiopterin metabolism in patients with phenylalanine hydroxylase deficiency - Nardecchia, Francesca; Blau, Nenad (European journal of pediatrics, 2017)
The tetrahydrobiopterin (BH4) cofactor is essential for the activity of various enzymes, including phenylalanine (Phe) hydroxylase. In phenylketonuria (PKU) patients, who are chronically exposed to high Phe levels, high urinary excretion of BH4 metabolites neopterin and biopterin is observed. The aim of this longitudinal study was to investigate consistence and variability of the urinary excretion of pterins (neopterin and biopterin) in PKU patients in relation to age and concomitant blood Phe and tyrosine levels. The study was based on the result of 274 pterin examinations (3-13 exams per subject) performed in 47 PKU patients (aged 6 days to 37 years). Multivariate analysis showed that urinary biopterin and neopterin excretion was affected by age and concomitant blood Phe concentration. The influence of blood Phe on both biopterin and neopterin levels was greater in patients younger than 4 months. Later on, interindividual variability was higher than intraindividual variability for both biopterin and neopterin. Conclusion: Common metabolic (blood Phe levels) and individual (age) factors implicated in the assessment of PKU outcome account only marginally and transiently for the variability of neopterin and biopterin excretion in PKU patients. Other unknown homeostatic factors may probably affect the individual response to chronically elevated Phe levels.